(untitled) (Research, Society and Development, 2023)
This study aimed to describe and characterize the biometry of the fruits, and seeds of three species of Solanum (Solanaceae) from the Amazonia. Biometry can help the development of efficient techniques for the management and understanding of the species. The morphometric characterization of the structures was performed from 100 fruits and 100 seeds, collected in the Metropolitan Region of Belém from the Amazonia. And analysis of the ornamentation of the seed scanning electron microscopy (SEM). The fruits are polyspermic, fleshy, berry-type, dehiscent, consisting of one or two locules with the seeds attached to the axial placenta, with five lobes on the end, glabrous, green when immature, purple and red in S. americanum and S. stramoniifolium and pulbescent greens in S. crinitum, when ripe. The seeds are obovoid to subdiscoid, little to very compressed. The forehead ornamentation is reticulated with straight to sinuous walls and the presence of filiform projections. Internally, the seeds are albuminous with a gelatinous endosperm surrounding the entire embryo of the axial type, continuous linear circined to imbricate. The weight of 1,000 seeds was higher for those in S. crinitum 2.36 g, followed by S. stramoniifolium with 1.67 g and S. americanum with 0.4 g.